Identification of Anatomy Contents for Medical Students Using DELPHI Technique - Siti Munawaroh; Gandes Retno Rahayu; Efrayim Suryadi (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2017)
Background: Anatomy is one of basic science in medicine. As doctors are obligated to assure their service is safe and efficient, they need to master anatomy science to support their work on comprehend the patient condition. In another condition, there is a shifting on medical curricula that impacted on decrease of anatomy instructional hours. This condition result in lower of anatomy academic achievement among medical students. The third of ten question Harden in curriculum development, that is what content should be included? need to be resolved so that the limited time available can be utilized as well as possible. This study aims to achieve national scope consensus among anatomical expert about anatomical material course that must be delivered to medical students.Method: This study was design in qualitative approach with specified method of two round Delphi Technique. Using purposive sampling method, the subject of study involved was 20 experts of anatomical science in Indonesia. The questionnaire as instrument in this study arranged based on anatomy text book. The first Delphi purpose to select the anatomical course material and additional course material. The second Delphi round intent to provide level range from 1-4. The consensus level established by the researcher at 80% point.Results: The first Delphi round result in 760 anatomy topics consist of 636 original material arranged by researcher and 124 additional material added by the Delphi panel. Additional materials are osteomyology and sesnsory system. The second Delphi round agree 64% material of first Delphi round (489).Conclusion: Indonesian anatomical experts agree in which not all of anatomy material need to be learned by medical student. Their consensus is about 64% of all the material that must be learned.